2022
DOI: 10.1177/20587384211066440
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin attenuates the proliferation, inflammation, and oxidative stress of high glucose-induced human mesangial cells by regulating the miR-485-5p/YAP1 pathway

Abstract: Background Diabetic nephropathy (DN) is a kidney damage caused by diabetes and the main cause of end-stage renal disease. However, the current treatment of DN has many limitations. Quercetin is a bioflavonoid compound with therapeutic benefits in metabolic diseases. This study aims to determine the therapeutic potentials and underlying mechanism of quercetin on DN. Methods We collected blood samples from DN patients and healthy controls and treated human mesangial cells (HMCs) with high glucose (HG) to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In our study, we found that the proliferation of HRMCs was promoted under HG condition, which was consistent with the results of previous studies (Wang et al, 2022; Zhu et al, 2021). Hyperglycemia‐induced oxidative stress has important roles in pathogenesis of diabetic nephropathy (Rosas‐Martínez et al, 2021; Vodosek Hojs et al, 2020), and HG could result in oxidative stress in renal mesangial cells (Wan et al, 2022; Wei et al, 2021). Similarly, our study showed that HG led to ROS production, MDA increase, and SOD activity reduction, suggesting that oxidative stress was induced by HG.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that the proliferation of HRMCs was promoted under HG condition, which was consistent with the results of previous studies (Wang et al, 2022; Zhu et al, 2021). Hyperglycemia‐induced oxidative stress has important roles in pathogenesis of diabetic nephropathy (Rosas‐Martínez et al, 2021; Vodosek Hojs et al, 2020), and HG could result in oxidative stress in renal mesangial cells (Wan et al, 2022; Wei et al, 2021). Similarly, our study showed that HG led to ROS production, MDA increase, and SOD activity reduction, suggesting that oxidative stress was induced by HG.…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes injury is one of the leading causes of proteinuria in patients with DKD, Liu et al found that quercetin can prevent glomerular damage in diabetic mice and repress podocyte apoptosis by inhibiting the EGFR signaling pathway [ 126 ]. A clinical study showed that the expression of miR-485-5p in peripheral blood of patients with DKD decreased significantly, through cell experiment, it was found that quercetin inhibited the expression of YAP1 by regulating the increase of miR-485-5p, thereby inhibiting HG-induced HMCs hyperproliferation, inflammation, and oxidative stress [ 127 ]. In addition, Du et al found that quercetin can also reduce the expression of yes-associated protein 1 (YAP1) by activating Hippo signaling pathway [ 128 ].…”
Section: Natural Compoundsmentioning
confidence: 99%
“…Quercetin is a flavonoid, which is a secondary metabolite of plant synthesis, and found in many fruits and vegetables ( 15 ). Quercetin has antioxidant and anti-inflammatory properties and modulates cell apoptosis, properties potentially of value in the treatment or prevention of mastitis ( 16 ). A previous research has shown that quercetin has an anti-cancer ability by inhibiting of growth of cells ( 17 ).…”
Section: Introductionmentioning
confidence: 99%